Adolescent Cranial Volume as a Sensitive Marker of Parental Investment: The Role of Non-material Resources? - Lauringson, Velda; Veldre, Gudrun; Hõrak, Peeter (Frontiers in Psychology, 2020)
Growth of different body parts of humans is sensitive to different resource constraints that are mediated by parental investment, i.e., expenditure of material, as well as cognitive and emotional resources, on offspring. Cranial volume, an important predictor of human performance, appears understudied in this context. We asked (1) whether we can detect associations between growth and family structure, self-reported estimates for resource availability, and sibling number; and (2) whether these constraints relate to the head and body growth in a similar manner. We assessed the associations between parental investment and height and cranial volume in a cross-sectional study of Estonian children (born 1980-87, aged 11-17). Controlling for birthweight, parental heights and mother’s age at birth, we found that the height of children was negatively associated with the number of siblings and that this trade-off was mediated by resource availability. Unlike height, cranial volume was independent of sibling number, but it was negatively associated with self-reported meat and general resource shortage and was related to family structure and paternal education. Children living with both birth-parents had larger heads than those living in families containing a step-parent. Since these family types did not differ with respect of meat or general resource shortage, our findings suggest that families including both genetic parents provide non-material benefits that stimulate predominantly cranial growth. For the studied developmental period, cranial volume appeared more sensitive marker of growth constraints than height. Its potential for quantification of physical impact of non-material parental investment deserves further attention.